The Influence of School Facilities Service Quality and Teacher Competency to the Satisfaction of Madrasah Aliyah Annajah Students Jakarta - Sari, Lestary Permata; Surip, Ngadino (International Journal for Educational and Vocational Studies, 2020)
This study aims to determine the effect of school facilities, service quality and teacher competence on student satisfaction. The research method used is a quantitative analysis method using multiple linear regression and analysis of determination (R square), partial hypothesis testing (t test) and simultaneous (F test) as well as correlation between dimensions with a population of 291 people and is based on the method of taking probability sampling with a simple random sampling technique with a precision of 10% and obtained a sample of 100 people. The results showed that there was a strong relationship between variables and dimensions as indicated by the correlation between dimensions in which school facilities influenced the positive and significant aesthetic dominant dimensions and were related to student satisfaction. Quality of service influences the tangible dimensions of the dominant positive and significant and is related to student satisfaction and teacher competence influences the dominant and significant pedagogic dimensions positively and is related to students satisfaction.